ANALISIS POTENSI SEKTOR UNGGULAN DAN PERGESERAN STRUKTUR PEREKONOMIAN DI KABUPATEN/KOTA PROVINSI BANTEN TAHUN 2011-2015 - Afrisal Dea Bagaskara; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2017)
This study entitled “Analysis of Potential of Superior Sector and Shifting of Economic Structure in Regencies / Cities in Banten Province Year 2011-2015.The economic growth is a process of changing the economic conditions of a region to a better state in a certain period. In order to carry out development is preferred to sectors that have special quality. The purpose of this research is to know the potential of Superior sector in Regency / City of Banten Province. This research uses panel data from Gross Domestic Product in Regency / City of Banten Province Year 2010-2015. The Analysis tool that used in this research is Location Quotient Analysis and Shift share Analysis.The result of Location Quotient Analysis can be known that sector which is superior in Regency / City of Banten Province still dominated by Education Service sector. The result of Shift Share Analysis can be seen from structural shift from secondary to tertiary. Then from the Classical SS table, SS Esteban-Marquillas and SS Archelus, that some districts in Banten Province have positive values on special quality competitive and regional specialization. The calculation of economic structure in the Regency / City of Banten Province shows the dominance of the tertiary sectors compared to the primary and secondary sectors.Keywords: Location Quotient, Superior sector, Shift share.